2019
DOI: 10.15826/jtr.2019.5.1.059
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis of Russian oil companies based on tax burden parameters

Abstract: The recent dramatic fall in oil prices has led to extensive capital rationing in international oil companies, and subsequent fierce competition between resource extraction countries to attract scarce investment. This situation is not adequately addressed by the large literature on international taxation and multinational companies, since it fails to take account of capital rationing in its assumption that companies sanction all projects with a positive net present value. The paper examines the effect of tax de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The main difference during this period was the impact of population dynamics on CO2 emissions. For example, if a population decline was recorded in Russia, then the OECD population increased, which had a positive effect on CO2 emissions [8][9][10][11] (Figure 3). However, in the last decade, Russia and the OECD countries are characterized by a significant difference in the structure of the increase in CO2 emissions:…”
Section: Discussionmentioning
confidence: 99%
“…The main difference during this period was the impact of population dynamics on CO2 emissions. For example, if a population decline was recorded in Russia, then the OECD population increased, which had a positive effect on CO2 emissions [8][9][10][11] (Figure 3). However, in the last decade, Russia and the OECD countries are characterized by a significant difference in the structure of the increase in CO2 emissions:…”
Section: Discussionmentioning
confidence: 99%
“…Fjaertoft and Lunden analyzed the policy of "tax maneuver" introduced in 2014 with real world field study, and concluded that it is poorly evaluated in terms of simplicity, flexibility, stability, and competitiveness [5]. Filimonova et al conducted cluster analysis on tax burden of Mineral Extraction Tax (MET) and export duty from 2010 to 2017 and proposed suggestions for petroleum tax reform in Russia [6].…”
Section: Introductionmentioning
confidence: 99%